Protein–protein interactions between SWCNT/chitosan/EGF and EGF receptor: a model of drug delivery system - Rungnim C. (2017)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. Epidermal growth factor (EGF) was used as the targeting ligand to enhance the specificity of a cancer drug delivery system (DDS) via its specific interaction with the EGF receptor (EGFR) that is overexpressed on the surface of some cancer cells. To investigate the intermolecular interaction and binding affinity between the EGF-conjugated DDS and the EGFR, 50 ns molecular dynamics simulations were performed on the complex of tethered EGFR and EGF linked to single-wall carbon nanotube (SWCNT) through a biopolymer chitosan wrapping the tube outer surface (EGFR·EGF-CS-SWCNT-Drug complex), and compared to the EGFR·EGF complex and free EGFR. The binding pattern of the EGF-CS-SWCNT-Drug complex to the EGFR was broadly compar able to that for EGF, but the binding affinity of the EGF-CS-SWCNT-Drug complex was predicted to be somewhat better than that for EGF alone. Additionally, the chitosan chain could prevent undesired interactions of SWCNT at the binding pocket region. Therefore, EGF connected to SWCNT via a chitosan linker is a seemingly good formulation for developing a smart DDS served as part of an alternative cancer therapy.